The Use of the Case/s Study and Reporting on Educational Research : Literature Review - Borzi, Sonia Lilian (Orientación y Sociedad.)
This work focuses on the use of Case Study (CS) in Educational Psychology research. It is part of the research project "Qualitative Research Designs in Psychology: characterization and integration of ethical and methodological aspects of Case Study" (2015-2016), whose central purpose is to perform a bibliographic descriptive exploratory study, type on the use of CS research designs from different fields of psychology. In this article we delve into aspects such designs in the field of psycho-educational research: proactive, interactive and postactiva that allow deepening problems or educational facts. In the development of the CS, three phases are identified. The last phase involves the definition of the EC as a product or result of a larger process: it involves reporting by biographical narratives-from the understanding of a fact, event, individual or group in its singularity forms. To this end, they have collected not only contextual descriptions, but also the voices of the subjects, allowing experience an "existential" sense of the case that favors both their understanding and the development of lessons learned for future interventions.